POLA PENDEKATAN DAN STRATEGI PEMBELAJARAN DALAM MENINGKATKAN MUTU MADRASAH - Nurul Inayah Bachmid; Burhanuddin Abdul Karim Mantau (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study discusses the application of Islamic Religious Education learning approaches and strategies in madrasahs with the aim of improving the quality of the teaching and learning process. The problem identified is that the selection and application of IRE learning approaches and strategies that are appropriate to the characteristics of students are not yet optimal, thus impacting the effectiveness of learning and the achievement of religious competencies. This study aims to analyze relevant and effective IRE approaches and strategies applied in madrasahs. The method used is library research with a qualitative approach, examining various literature from books, articles, and other scientific sources related to the study. The results of the study show that relevant approaches include habituation, rational, emotional, functional, and exemplary, while effective learning strategies include character-based, inquiry, storytelling, Contextual Teaching and Learning (CTL), and Modeling the Way. The application of these approaches and strategies is expected to increase students' activity, creativity, and critical thinking skills, while also shaping internalized Islamic character and morals. The combination of the right approaches and strategies makes PAI learning not only a transfer of knowledge, but also a means of shaping students' religious personalities and spiritual, social, and cognitive competencies.